External load application in gait and posture reeducation after diffuse axonal injury of the corpus callosum. A case report - Zawadka, Magdalena; Kochman, Maciej; Sobiech, Magdalena; Jabłoński, Mirosław (Journal of Education, Health and Sport, 2018)
Traumatic brain injury caused car accidents is the one of the most common causes of diffuse axonal injury typically located at the grey-white matter junction, in the corpus callosum. A 58-year-old female patient Caucasian race was admitted to the Orthopedic and Rehabilitation Unit with head injury, broken right ulnar bone, numerous broken ribs and broken right iliac crest. Neurological examination resulted in right-sided hemiparesis. There were also coordination and balance disorders while sitting and standing. The patient was unable to walk. After physiotherapy treatment included external load application (ankle weights and rucksack with weights) in gait and posture reeducation, patient has improved balance, locomotion and body posture. However, application of external loads during walk and posture reeducation needs to be further investigated with greater number of participants and control group.